Morphological, morphometrical and histological characteristics of Menisci in domestic cats (Felis catus) - Zabiddin, Nur Izzati Inani; Bakar, Md Zuki Abu; Noor, Mohd Akmal Mohd; Ghazali, Mohd Faizal; Chai, Min Hian; Azman, Dhiya Athirah; Ariffin, Siti Mariam Zainal (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2024)
This study aimed to investigate the morphological and morphometric features, as well as the histological composition of the medial and lateral menisci of domestic cats. A total of 180 menisci were obtained from 45 skeletally mature cat cadavers, followed by measuring the peripheral extension, width and thickness, circumference of the body and the body with horns, articulating height, and superior articulating length. A histological assessment was conducted to determine the meniscal cellularity and histomorphology. Each meniscus was evaluated in three regions (cranial horn, body, and caudal horn) and three zones (outer, middle, and deep). The proteoglycan content and collagen distribution were also examined. Overall, 62.2% of the medial meniscus displayed a crescentic shape, whereas 86.7% of the lateral meniscus exhibited a C-shaped configuration. The morphometric analysis revealed that the lateral menisci significantly differed (P<0.05) in circumference, thickness, width, and articulating height from the medial menisci. Despite cell density was not significantly different across the regions, the cellularity decreased from the outer zone to the deep zone of the menisci. Proteoglycan content was not significantly different in the various regions but was increased significantly (P<0.05) in the middle meniscal zone. Types I, II, and III collagens were distributed throughout the meniscal regions and zones. Type I collagen was abundant within the meniscus. In contrast, type III collagen is primarily localized in the middle zone. In conclusion, feline menisci exhibit morphometric variations and distinctive histological features, offering crucial insights for veterinarians and researchers.